Vitamin D as a Modifiable Risk Factor for NAFLD in T2DM patients - Kiran Akhtar,Mariam Aftab Farah Naz Tahir, Laiba Hamid, Mishal Rizwan, Zahra Farooq Aliza Ahsan, Haris Bin Khalid Kainat Amir, Khushnaseeb Aziz (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
To investigate the role of vitamin D as a modifiable risk factor for NAFLD in type 2diabetes mellitus patients, exploring its potential impact on NAFLD development, progression,and management. Overall 200 patients with TD2M